Prediction of VO2max based on a 3-kilometer running test for water sports athletes - Gao, W. D.; Zheng, P. P.; Pan, J. W.; Fang, H. B.; Kan, J.; Chen, Q. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: No studies have reported the 3-kilometer running test (3KRT) intending to predict VO2max for water sports athletes. Therefore, the purpose of this study was to develop a new model to predict the maximal aerobic capacity (VO2max) for water sports athletes based on 3KRT. METHODS: One hundred and two water sports athletes completed two sessions of experiments consisting of a maximal graded exercise test (GXT) and a 3KRT. Multiple linear regression was applied to predict VO2max value based on the performance and physiological responses of 3KRT, along with participants` anthropometric and demographic variables. The predicted residual error sum of square (PRESS) and error terms (constant error and total error) were calculated to further evaluate the predictive accuracy. RESULTS: Two significant prediction models based on elapsed exercise time (T3KRT), post-exercise heart rate (PHR3KRT), body mass, and gender were proposed. One model including PHR3KRT was identified (VO2max=120.77-0.028×T3KRT [second]-0.11×PHR3KRT [bpm]-0.334×body mass [kg]+8.70×gender [1: male, 0: female]), with an adjusted R2 of 0.723. Another model excluding PHR3KRT was also identified (VfO2max=103.65-0.034×T3KRT [second]-0.317×Body mass [kg] + 7.89×gender [1: male, 0: female]), with an adjusted R2 of 0.713. Both models were further validated by the result of PRESS statistics. CONCLUSIONS: This endurance 3-kilometer running test accurately predicted VO2max value for water sports athletes (rowers, canoeists, and kayakers), and the model excluding PHR3KRT would be easier to use.